2023
DOI: 10.3390/cancers15061640
|View full text |Cite
|
Sign up to set email alerts
|

Mucins as Potential Biomarkers for Early Detection of Cancer

Abstract: Early detection significantly correlates with improved survival in cancer patients. So far, a limited number of biomarkers have been validated to diagnose cancers at an early stage. Considering the leading cancer types that contribute to more than 50% of deaths in the USA, we discuss the ongoing endeavors toward early detection of lung, breast, ovarian, colon, prostate, liver, and pancreatic cancers to highlight the significance of mucin glycoproteins in cancer diagnosis. As mucin deregulation is one of the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 316 publications
(411 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, the surface elemental compositions of the 1 -PEDOT composite film were also tested by XPS (Figure c). Comparing the XPS survey of 1 and the 1 -PEDOT composite film, we can observe that both the characteristic peaks from 1 (W 4f: 36.1 and 35.0 eV, and Ce 3d: 885.0 and 884.1 eV) and those corresponding to PEDOT (S 2p: 163.5 and 164.6 eV) simultaneously appear in the XPS pattern of the 1 -PEDOT film. In addition, the SEM images were utilized to characterize and compare the surface morphologies of the PEDOT film and the 1 -PEDOT composite film. As shown in Figure d, the polymerized PEDOT film in the absence of 1 demonstrates a bumpy and rough morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the surface elemental compositions of the 1 -PEDOT composite film were also tested by XPS (Figure c). Comparing the XPS survey of 1 and the 1 -PEDOT composite film, we can observe that both the characteristic peaks from 1 (W 4f: 36.1 and 35.0 eV, and Ce 3d: 885.0 and 884.1 eV) and those corresponding to PEDOT (S 2p: 163.5 and 164.6 eV) simultaneously appear in the XPS pattern of the 1 -PEDOT film. In addition, the SEM images were utilized to characterize and compare the surface morphologies of the PEDOT film and the 1 -PEDOT composite film. As shown in Figure d, the polymerized PEDOT film in the absence of 1 demonstrates a bumpy and rough morphology.…”
Section: Resultsmentioning
confidence: 99%
“…59−63 Mucins are a family of high-molecular-weight and heavily glycosylated proteins, in which mucin 1 as the most studied mucin has been recognized as one of the most common biomarkers for the early diagnosis of human cancers. 64,65 Moreover, it is found that POMs and PEDOT composite materials have been used in some fields such as solar cells, optoelectronic devices, electrocatalysis, and electrochromism. 66−69 However, POM− PEDOT composite films as substrates for electrochemical sensors are very rare.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bone marrow stromal antigen-2/CD317/Tetherin (BST2), Folate receptor alpha (FOLR1), and Mucin-1 (MUC1) are cell surface proteins previously shown to be overexpressed in ovarian cancer (Gautam et al, 2023; Giampaolino et al, 2020, 2019; Januchowski et al, 2017; Kufe, 2009; Trinidad et al, 2023; Varaganti et al, 2023; Yang et al, 2022). Protein expression of all three biomarkers was demonstrated by western blotting to be present in the EV fractions from human ovarian cancer cell lines (Figure 2) and human plasma (not shown) enriched by size exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The probe has shown effectiveness in binding to human pancreatic cancer cell lines in both laboratory settings and living organisms. [81] [82] [83]…”
Section: Introductionmentioning
confidence: 99%
“…The probe has shown effectiveness in binding to human pancreatic cancer cell lines in both laboratory settings and living organisms. [81] [82] [83] Ribonucleotide reductase catalytic subunit M1 (RRM1) has been identified in datasets associated with gemcitabine. It has been observed that the expression of RRM1 is notably elevated in pancreatic cancer tissue as well as in cells resistant to gemcitabine in both laboratory and living organism settings settings.…”
Section: Introductionmentioning
confidence: 99%